Missing Nurse Bees—Early Transcriptomic Switch From Nurse Bee to Forager Induced by Sublethal Imidacloprid - Chen, Yun-Ru; Tzeng, David T. W.; Ting, Chieh; Hsu, Pei-Shou; Wu, Tzu-Hsien; Zhong, Silin; Yang, En-Cheng (Frontiers in Genetics, 2021)
The environmental residue/sublethal doses of neonicotinoid insecticides are believed generating negative impact on pollinators, including honey bees. Here we report our recent investigation on how imidacloprid, one of the major neonicotinoids, affects worker bees by profiling the transcriptomes of various ages of bees exposed to different doses of imidacloprid during the larval stage. The results show that imidacloprid treatments during the larval stage severely altered the gene expression profiles and may induced precocious foraging. Differential expression of foraging regulators were found in 14-day-old treated adults. High transcriptome similarity between larvae-treated 14-day-old adults and 20-day-old controls was also observed, and the similarity was positively correlated with the dose of imidacloprid. One part per billion (ppb) imidacloprid was sufficient to generate a long-term impact on the bee’s gene expression as severe as with 50 ppb imidacloprid. The disappearance of nurse bees may be driven not only by the hive member constitution but also by the neonicotinoid-induced precocious foraging behavior.